THE USE OF FLASH CARDS APPLICATION IN TEACHING VOCABULARY - Yusril, Ulfa Sakinah; Jabu, Baso; Muliati, A. (Universitas Negeri Makassar, 2022)
This research highlights the use of flashcards application in teaching vocabulary. The study's goals were to discover how students' vocabulary may be improved by utilizing flashcards programs. To fulfill the aims, the researcher performed classroom action research, with 30 students chosen using a purposive selection approach as participants. The result of this research was gathered by multiple tests, they were pretest, a cycle 1 test, a cycle 2 test, and a post-test. The result of this research showed that most of the students had an improvement in learning vocabulary using a flashcard application in the pretest the students could not reach the KKM score, they only could attain 49.00 but after learning using the flashcard application, they achieved 1990 (63.33) for cycle 1 test, 2515 (83.83) for cycle 2 test and 2766 (92.2) for the final posttest.